Aggregated neutrophil extracellular traps resolve inflammation by proteolysis of cytokines and chemokines and protection from antiproteases - Hahn, Jonas; Schauer, Christine; Czegley, Christine; Kling, Lasse; Petru, Lenka; Schmid, Benjamin; Weidner, Daniela; Reinwald, Christiane; Biermann, Mona H.C.; Blunder, Stefan; Ernst, Jurgen; Lesner, Adam; et al. (The FASEB Journal, 2018)
Papillon-Lefèvre syndrome (PLS) is characterized by nonfunctional neutrophil serine proteases (NSPs) and fulminant periodontal inflammation of unknown cause. Here we investigated neutrophil extracellular trap (NET)-associated aggregation and cytokine/chemokine-release/degradation by normal and NSP-deficient human and mouse granulocytes. Stimulated with solid or soluble NET inducers, normal neutrophils formed aggregates and both released and degraded cytokines/chemokines. With increasing cell density, proteolytic degradation outweighed release. Maximum output of cytokines/chemokines occurred mostly at densities between 2 × 107 and 4 × 107 neutrophils/cm3. Assessment of neutrophil density in vivo showed that these concentrations are surpassed during inflammation. Association with aggregated NETs conferred protection of neutrophil elastase against α1-antitrypsin. In contrast, eosinophils did not influence cytokine/chemokine concentrations. The proteolytic degradation of inflammatory mediators seen in NETs was abrogated in Papillon-Lefèvre syndrome (PLS) neutrophils. In summary, neutrophil-driven proteolysis of inflammatory mediators works as a built-in safeguard for inflammation. The absence of this negative feedback mechanism might be responsible for the nonresolving periodontitis seen in PLS.-Hahn, J., Schauer, C., Czegley, C., Kling, L., Petru, L., Schmid, B., Weidner, D., Reinwald, C., Biermann, M. H. C., Blunder, S., Ernst, J., Lesner, A., Bäuerle, T., Palmisano, R., Christiansen, S., Herrmann, M., Bozec, A., Gruber, R., Schett, G., Hoffmann, M. H. Aggregated neutrophil extracellular traps resolve inflammation by proteolysis of cytokines and chemokines and protection from antiproteases.
EVALuna2:34668

A model of chronic enthesitis and new bone formation characterized by multimodal imaging - Czegley, Christine; Gillmann, Clarissa; Schauer, Christine; Seyler, Lisa; Reinwald, Christiane; Hahn, Madelaine; Uder, Michael; Jochmann, Katja; Naschberger, Elisabeth; Stock, Michael; Schett, Georg; Bäuerle, Tobias; et al. (Disease Models & Mechanisms, 2018)
Enthesitis is a key feature of several different rheumatic diseases. Its pathophysiology is only partially known due to the lack of access to human tissue and the shortage of solid animal models for enthesitis. Here we aimed to develop a model, which mimics the effector phase of enthesitis and reliably leads to inflammation and new bone formation.Enthesitis was induced by local injection of monosodium urate crystals (MSU) into the metatarsal entheses of wild type (WT) or oxidative burst-deficient Ncf1** mice. Quantitative variables of inflammation (edema, swelling) and vascularization (tissue perfusion) were assessed by MRI, bone forming-activity by [18F]-fluoride-PET and destruction of cortical bone and new bone formation by CT. Non-invasive imaging was validated by histochemical and histomorphometric analysis.While injection of MSU crystals into WT mice triggered transient mild enthesitis with no new bone formation, Ncf1** mice developed chronic enthesitis accompanied by massive enthesiophytes. In MRI, inflammation and blood flow in the entheses were chronically increased while PET/CT showed osteoproliferation with enthesiophyte formation. Histochemical analyses showed chronic inflammation, increased vascularization, osteoclast differentiation and bone deposition in the affected entheseal sites.Herein we describe a fast and reliable effector model of chronic enthesitis, which is characterized by a combination of inflammation, vascularization and new bone formation. This model will help to disentangle the molecular pathways involved in the effector phase of enthesitis.
EVALuna2:34481

Corrigendum: Oxidative burst-dependent NETosis is implicated in the resolution of necrosis-associated sterile inflammation (Frontiers in Immunology, (2016), 7, (557), 10.3389/fimmu.2016.00557) - Biermann, Mona Helena Camilla; Podolska, Malgorzata; Knopf, Jasmin; Reinwald, Christiane; Weidner, Daniela; Maueröder, Christian; Hahn, Jonas; Kienhöfer, Deborah; Barras, Alexandre; Boukherroub, Rabah; Szunerits, Sabine; Bilyy, Rostyslav; et al. (Frontiers in Immunology, 2025)
In the published article, there was an error in Supplementary Figure S1B as published. Supplementary Figure S1B of this Figure included by mistake a TEM image of a ND finally not used in this work. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2025-04-18
Keywords: inflammation; nanodiamonds; necrosis; NETosis; reactive oxygen species; resolution

Experimental lupus is aggravated in mouse strains with impaired induction of neutrophil extracellular traps - Kienhofer, Deborah; Hahn, Jonas; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Urbonaviciute, Vilma; Johnsson, Caroline; Maueröder, Christian; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; Harrer, Thomas; et al. (JCI Insight, 2017)
Many effector mechanisms of neutrophils have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). Neutrophil extracellular traps (NETs) have been assigned a particularly detrimental role. Here we investigated the functional impact of neutrophils and NETs on a mouse model of lupus triggered by intraperitoneal injection of the cell death-inducing alkane pristane. Pristane-induced lupus (PIL) was aggravated in 2 mouse strains with impaired induction of NET formation, i.e., NOX2-deficient (Ncf1-mutated) and peptidyl arginine deiminase 4-deficient (PAD4-deficient) mice, as seen from elevated levels of antinuclear autoantibodies (ANAs) and exacerbated glomerulonephritis. We observed a dramatically reduced ability to form pristane-induced NETs in vivo in both Ncf1-mutated and PAD4-deficient mice, accompanied by higher levels of inflammatory mediators in the peritoneum. Similarly, neutropenic Mcl-1ΔMyelo mice exhibited higher levels of ANAs, which indicates a regulatory function in lupus of NETs and neutrophils. Blood neutrophils from Ncf1-mutated and human individuals with SLE exhibited exuberant spontaneous NET formation. Treatment with specific chemical NOX2 activators induced NET formation and ameliorated PIL. Our findings suggest that aberrant NET is one of the factors promoting experimental lupus-like autoimmunity by uncontrolled release of inflammatory mediators.
EVALuna2:1833

No evidence of pathogenic involvement of cathelicidins in patient cohorts and mouse models of lupus and arthritis - Kienhofer, D.; Hahn, Jonas; Schubert, I.; Reinwald, Christiane; Ipseiz, N.; Lang, Sabine; Borras, E. Bosch; Amann, Kerstin Ute; Sjowall, C.; Barron, A. E.; Hueber, Axel; Agerberth, B.; et al. (PLoS ONE, 2014)
Apart from their role in the immune defence against pathogens evidence of a role of antimicrobial peptides (AMPs) in autoimmune diseases has accumulated in the past years. The aim of this project was to examine the functional impact of the human cathelicidin LL-37 and the mouse cathelicidin-related AMP (CRAMP) on the pathogenesis of lupus and arthritis. Serum LL-37 and anti-LL-37 levels were measured by ELISA in healthy donors and patients with Systemic Lupus Erythematosus (SLE) and Rheumatoid arthritis (RA). Pristane-induced lupus was induced in female wild type (WT) and cathelicidin-deficient (CRAMP-/-) mice. Serum levels of anti-Sm/RNP, anti-dsDNA, and anti-histone were determined via ELISA, cytokines in sera and peritoneal lavages were measured via Multiplex. Expression of Interferon I stimulated genes (ISG) was determined by real-time PCR. Collagen-induced arthritis (CIA) was induced in male WT and CRAMP-/- mice and arthritis severity was visually scored and analysed histomorphometrically by OsteoMeasure software. Serum levels of anti-LL-37 were higher in SLE-patients compared to healthy donors or patients with RA. However, no correlation to markers of disease activity or organ involvement was observed. No significant differences of autoantibody or cytokine/chemokine levels, or of expression of ISGs were observed between WT and CRAMP-/- mice after pristane-injection. Furthermore, lung and kidney pathology did not differ in the absence of CRAMP. Incidence and severity of CIA and histological parameters (inflammation, cartilage degradation, and bone erosion) were not different in WT and CRAMP-/- mice. Although cathelicidins are upregulated in mouse models of lupus and arthritis, cathelicidin-deficiency did not persistently affect the diseases. Also in patients with SLE, autoantibodies against cathelicidins did not correlate with disease manifestation. Reactivity against cathelicidins in lupus and arthritis could thus be an epiphenomenon caused by extensive overexpression in blood and affected tissues. In addition, other cationic AMPs could functionally compensate for the deficiency of cathelicidins.
EVALuna2:12499

Oxidative Burst-Dependent NETosis Is Implicated in the Resolution of Necrosis-Associated Sterile Inflammation - Biermann, Mona Helena Camilla; Podolska, Malgorzata; Knopf, Jasmin; Reinwald, Christiane; Weidner, Daniela; Maueröder, Christian; Hahn, Jonas; Kienhoefer, Deborah; Barras, Alexandre; Boukherroub, Rabah; Szunerits, Sabine; Bilyy, Rostyslav; et al. (Frontiers in Immunology, 2016)
Necrosis is associated with a profound inflammatory response. The regulation of necrosis-associated inflammation, particularly the mechanisms responsible for resolution of inflammation is incompletely characterized. Nanoparticles are known to induce plasma membrane damage and necrosis followed by sterile inflammation. We observed that injection of metabolically inert nanodiamonds resulted in paw edema in WT and Ncf1** mice. However, while inflammation quickly resolved in WT mice, it persisted over several weeks in Ncf1** mice indicating failure of resolution of inflammation. Mechanistically, NOX2-dependent reactive oxygen species (ROS) production and formation of neutrophil extracellular traps were essential for the resolution of necrosis-induced inflammation: hence, by evaluating the fate of the particles at the site of inflammation, we observed that Ncf1** mice deficient in NADPH-dependent ROS failed to generate granulation tissue therefore being unable to trap the nanodiamonds. These data suggest that NOX2-dependent NETosis is crucial for preventing the chronification of the inflammatory response to tissue necrosis by forming NETosis-dependent barriers between the necrotic and healthy surrounding tissu
EVALuna2:13386

Reply to "Neutrophils are not required for resolution of acute gouty arthritis in mice" - Reinwald, Christiane; Schauer, Christine; Csepregi, Janka Zsofia; Kienhoefer, Deborah; Weidner, Daniela; Malissen, Marie; Mocsai, Attila; Schett, Georg; Herrmann, Martin; Hoffmann, Markus (Nature Medicine, 2016)
EVALuna2:13379

Reset of inflammatory priming of joint tissue and reduction of the severity of arthritis flares by bromodomain inhibition - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al. (Arthritis and Rheumatology, 2023)
Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extra-terminal motif (BET) proteins translate epigenetic changes into transcription. Here we used a BET inhibitor to target inflammatory tissue priming and reduce flare severity in experimental arthritis. Methods: BALB/c mice were treated intraperitoneally or locally into the paw with I-BET151, which blocks interaction of BET proteins with acetylated histones. Effect of I-BET151 on acute arthritis and/or inflammatory tissue priming was assessed in a model of repeated injections of monosodium urate crystals or zymosan into the paw. I-BET151 was given either from before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. Transcriptomic (RNA-Seq), epigenomic (ATAC-Seq) and functional analysis (invasion, cytokine production, migration, senescence, metabolic flux) was performed on murine and human SFs treated with I-BET151 in vitro or in vivo. Results: Systemic I-BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I-BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, which makes them promising therapeutic targets for preventing arthritis flares in previously affected joints.
CRIS-Team Scopus Importer:2023-01-27

ROS is the boss - Hahn, Jonas; Kienhofer, Deborah; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Maueröder, Christian; Urbonaviciute, Vilma; Munoz, Luis Enrique; Hultqvist, Malin; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; et al. (2017)
EVALuna2:13467

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

To NET or not to NET: current opinions and state of the science regarding the formation of neutrophil extracellular traps - Boeltz, Sebastian; Amini, Poorya; Anders, Hans-Joachim; Andrade, Felipe; Bilyy, Rostyslav; Chatfield, Simon; Cichon, Iwona; Clancy, Danielle M.; Desai, Jyaysi; Dumych, Tetiana; Dwivedi, Nishant; Gordon, Rachael Ann; et al. (Cell Death and Differentiation, 2019)
Since the discovery and definition of neutrophil extracellular traps (NETs) 14 years ago, numerous characteristics and physiological functions of NETs have been uncovered. Nowadays, the field continues to expand and novel mechanisms that orchestrate formation of NETs, their previously unknown properties, and novel implications in disease continue to emerge. The abundance of available data has also led to some confusion in the NET research community due to contradictory results and divergent scientific concepts, such as pro- and anti-inflammatory roles in pathologic conditions, demarcation from other forms of cell death, or the origin of the DNA that forms the NET scaffold. Here, we present prevailing concepts and state of the science in NET-related research and elaborate on open questions and areas of dispute.
CRIS-Team WoS Importer:2019-02-22